Alternative Use of Tamarind Pretreatment in Making Eggshell Flour - Ayutha Wijinindyah; Jerry Selvia; Husnul Chotimah; Ida Ketut Mudhita (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2022)
The use of acid pretreatment in the manufacture of eggshell flour is an alternative way to speed up drying time, reduce product odor, and facilitate the absorption of nutrients when consumed. Tamarind is one type of acidifying agent that is widely available around, both sold commercially and naturally. This study aims to examine the differences in the use of various types of tamarind pretreatment in the process of making eggshell flour. The type of acid used as pretreatment was Tamarind in Lombok, Kalimantan, and Java. The method of this research is to soak egg shells with various types of tamarind mentioned above for 3 (three) hours. Parameters observed were proximate analysis (water content, ash, fat, protein, crude fiber, carbohydrates) and minerals (calcium and phosphorus), pH and yield. The results show that there are differences in the administration of acid pretreatment to the observed parameters. The results of the treatment showed that the best proximate value was obtained in the Lombok tamarind pretreatment and the main control, as well as the yield and calcium levels. The best value of phosphorus content was in the use of Lombok tamarind pretreatment and the main control.